2007
DOI: 10.4028/www.scientific.net/msf.550.223
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Deformation Microstructure and Subsequent Recrystallisation in Hot Deformed Aluminium Alloy AA5052 Using Forward and Reverse Torsion

Abstract: The effects of strain path reversal on the microstructure in AA5052 have been studied using high resolution EBSD. Deformation was carried out using two equal steps of forward/forward (F/F) or forward/reverse (F/R) torsion at a temperature of 300°C and strain rate of 1s-1 to a total strain of 0.5. In both cases the deformation microstructure in the majority of grains analysed consisted of microband arrays clustering at specific angles to the macroscopic deformation axes. For the F/F condition microbands cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…3a) the material has recrystallised with a finer grain structure whereas for the F/R condition (Fig. 3c) there is no recrystallisation which is confirmed by the grain size measurements which indicate virtually no change in grains size between the deformed material (60 µm) and the annealed material (81 This further confirms the results of many workers who have shown that a reversal in strain path retards recrystallisation for both dynamic [4-6] and static [7,8] recrystallisation.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…3a) the material has recrystallised with a finer grain structure whereas for the F/R condition (Fig. 3c) there is no recrystallisation which is confirmed by the grain size measurements which indicate virtually no change in grains size between the deformed material (60 µm) and the annealed material (81 This further confirms the results of many workers who have shown that a reversal in strain path retards recrystallisation for both dynamic [4-6] and static [7,8] recrystallisation.…”
Section: Resultssupporting
confidence: 83%
“…In this case there are significant differences between the two microstructures with the grain size of the F/F material much smaller than the F/R material, an exact comparison of the grain sizes is given in Table1. This observation plus the data in Table1implies that for the F/F condition (Fig.3a) the material has recrystallised with a finer grain structure whereas for the F/R condition (Fig.3c) there is no recrystallisation which is confirmed by the grain size measurements which indicate virtually no change in grains size between the deformed material (60 µm) and the annealed material (81 This further confirms the results of many workers who have shown that a reversal in strain path retards recrystallisation for both dynamic [4-6] and static[7,8] recrystallisation.A more quantitative analysis of the deformed and annealed materials is given in Fig.4, which plots the misorientation angle distribution for the different process conditions. For both deformed .…”
supporting
confidence: 83%